IMPLEMENTASI PERENCANAAN STRATEGI KINERJA GURU DALAM MENINGKATKAN MUTU PENDIDIKAN SMP NEGERI 1 KALIREJO - Malihatun (UNISAN JURNAL, 2024)
The implementation of strategic planning in the world of education is very urgent in facing quality competition in the modern era. Especially when improving quality has become competition. Awareness of the importance of education has resulted in the emergence of educational institutions as a result of advances in information and technology. This research is focused on obtaining an overview of data in the field regarding the implementation of strategic planning in improving the quality of teaching staff at SMP Negeri 1 Kalirejo District. Kalirejo District. Central Lampung. The data collection technique used in this research is field techniques. Implementation of strategic planning at SMP Negeri 1 Kalirejo includes three main steps, namely strategic planning, strategic planning implementation, and strategic planning evaluation. Implementation of the strategic plan at SMP Negeri 1 Kalirejo includes several actions such as preparation for implementing activities by holding meetings to determine the activities to be implemented and the main targets of the activities as well as the person responsible for the activities and its members. Strategic strategic evaluations are held periodically.